Competing Motivations in Grammar and Usage 2014
DOI: 10.1093/acprof:oso/9780198709848.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

A statistical model of competing motivations affecting relative clause extraposition in German

Abstract: Relative clause extraposition has been studied by both generativists and functionalists. Whereas generativists have concentrated on structural and semantic factors, such as syntactic locality, definiteness, and restrictiveness, functionalists have investigated surface‐oriented factors, like the length of the relative clause and the distance between it and its antecedent. Most studies, however, have only looked at individual factors and not tried to account for extraposition as a syntactic alternation using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
2
10
2
Order By: Relevance
“…Using corpus data from Heavy NP Shift and the prepositional/ double-object alternation in English, he found that predictions based on length in words and predictions based on number of syntactic nodes dominated were so highly correlated as to be virtually indistinguishable. Some subsequent studies have shown that structural embedding can have subtle but independent eff ects (Strunk, 2014 ;Wasow & Arnold, 2005 ). Here, though, we follow the majority of current studies and operationalize grammatical weight as phrase length in words.…”
Section: Gr Ammatical Weight Discourse Factors and Sentence Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…Using corpus data from Heavy NP Shift and the prepositional/ double-object alternation in English, he found that predictions based on length in words and predictions based on number of syntactic nodes dominated were so highly correlated as to be virtually indistinguishable. Some subsequent studies have shown that structural embedding can have subtle but independent eff ects (Strunk, 2014 ;Wasow & Arnold, 2005 ). Here, though, we follow the majority of current studies and operationalize grammatical weight as phrase length in words.…”
Section: Gr Ammatical Weight Discourse Factors and Sentence Processingmentioning
confidence: 99%
“…However, diff erent studies have used diff erent methods of measuring such eff ects. This section considers which measures of grammatical weight are most useful for predicting phrasal ordering preferences, with an emphasis on RCE in English (Francis, 2010 ;Francis & Michaelis, 2014 ) and German (Konieczny, 2000 ;Strunk, 2014 ;Uszkoreit et al, 1998 ). First, it should be noted that there are a few diff erent ways in which weight can be measured, including syllables, words, and syntactic nodes.…”
Section: Gr Ammatical Weight Discourse Factors and Sentence Processingmentioning
confidence: 99%
See 3 more Smart Citations